PENGUKURAN KINERJA SUPPLY CHAIN DENGAN PENDEKATAN METODE SCOR (SUPPLY CHAIN OPERATIONS REFERENCE) STUDI KASUS DI PT XYZ - Jejen Zaenal Mutaqin; Sutandi Sutandi (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
Indonesia's non-migas industries will play a key role in improving economic impact for the country, as it is consistent with the gross domestic product (wb) of non-migas industries. In the meantime, there are some negative effects that are mitigated, one of which is to the environment, in which a company must be required to increase its corporate performance in order to keep up with the competition and still look at the impact of the environment. As for the method of supply chain management using scor approach methods. Because beyond getting a knowledge of the company's performance from the intermal process, measuring performance using company scor methods has also been able to recognize the company's environmental performance, it can also increase attention to a wide range of negaific impacts that would affect the life cycles of the company's xyz corporation, a packaged alcohol corporation that already has food and environmental security standards, Yet this company has never been able to consolidate green supphy chain management. The company's repairs on this study have yet to be determined by researchers measuring the kincing of the supply chain using scor method approaches, which, in turn, have been supported by ahp sound and value in standardization by snorm DE Boer to get more accurate results. From the calculations presented at trafic light, the company's performance of 89 31 means that the company's performance is good but there are 4 kpi units of 21 PI that fall in the red category which means that all four must be made in the red category With the cooperation of both verbal and non-verbal partners, socializing with their employees can also replace energy-efficient sensors. And exercised regular control over the raw materials and the correct scheduling flow of information and material flow.